2020
DOI: 10.1111/jpc.14764
|View full text |Cite
|
Sign up to set email alerts
|

Perceived fatigue in children and young adults with neurofibromatosis type 1

Abstract: Aim This study describes the prevalence and severity of perceived fatigue in a young neurofibromatosis type 1 (NF1) population. Methods Ethical approval was obtained and NF1 affected Individuals aged 2–18 years from the Manchester's NF1 clinic invited along with any unaffected siblings. The PedsQL Multidimensional Fatigue Scale Parental and child report was used. This validated measure explores cognitive, physical and sleep/rest domains on a 0–100 scale. Higher scores indicate less fatigue. Fatigue scores in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…In our cohort PBTS with NF-1 reported increased general fatigue compared to those without NF-1, which was expected because children with NF-1 reported more perceived fatigue. 29 …”
Section: Discussionmentioning
confidence: 99%
“…In our cohort PBTS with NF-1 reported increased general fatigue compared to those without NF-1, which was expected because children with NF-1 reported more perceived fatigue. 29 …”
Section: Discussionmentioning
confidence: 99%
“…However, other studies have reported worse perception of HRQoL in females affected by chronic diseases 45,46 . The perception of fatigue in chronic conditions might be influenced by different gender‐related social behaviors, but further studies are required to clarify the association between fatigue and gender in chronic ITP 28,30,38 …”
Section: Discussionmentioning
confidence: 95%
“…The PedsQL Multidimensional Fatigue Scale (PedsQL MFS) is a generic symptom‐specific tool to measure fatigue in healthy children and adolescents as well as those with acute and chronic health conditions 26,27 . Importantly, it also measures cognitive fatigue, which focuses on memory and attention difficulties 28–30 . The use of these tools can be useful in clinical routine, because patients with ITP often report fatigue symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Children with NF1 display delayed motor development [17], which is associated with impaired bone loading and resultant deficits in skeletal development through childhood [18]. Previous studies have also identified muscle weakness in children with NF1 [19][20][21], although there is limited evidence of how this develops across childhood [20]. To date, we are only aware of one study which assessed physical activity in children with NF1, finding no difference from controls [19], but this was based on questionnaire assessments which may be less accurate and more prone to bias than objective accelerometer measures.…”
Section: Discussionmentioning
confidence: 99%